2015
DOI: 10.1021/jp509906m
|View full text |Cite
|
Sign up to set email alerts
|

Energy Propagation and Network Energetic Coupling in Proteins

Abstract: Understanding how allosteric proteins respond to changes in their environment is a major goal of current biological research. We show that these responses can be quantified by analyzing protein energy networks using a method recently developed in our group. On the basis of this method, we introduce here a quantity named energetic coupling, which we show is able to discriminate allosterically active mutants of the lactose repressor (LacI) protein, and of the catabolite activator protein (CAP), a dynamically dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 61 publications
1
64
0
2
Order By: Relevance
“…This is usually done based on interresidue distances and correlation coefficients extracted from MD simulations. We have recently shown that this approach introduces significant statistical errors in the analysis, and networks constructed in this way were not able to identify residues important for signal propagation in the protein imidazole glycerol phosphate synthase (21) or discriminate allosterically active mutants of the lactose repressor protein (22). On the other hand, we showed that assigning network edges based on interaction energies extracted from MD simulations can give an accurate description of signal propagation in proteins (21).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…This is usually done based on interresidue distances and correlation coefficients extracted from MD simulations. We have recently shown that this approach introduces significant statistical errors in the analysis, and networks constructed in this way were not able to identify residues important for signal propagation in the protein imidazole glycerol phosphate synthase (21) or discriminate allosterically active mutants of the lactose repressor protein (22). On the other hand, we showed that assigning network edges based on interaction energies extracted from MD simulations can give an accurate description of signal propagation in proteins (21).…”
Section: Introductionmentioning
confidence: 93%
“…The network coupling, recently introduced by our group (22), is a measure of the efficiency of signal propagation through the network. It uses a network efficiency measure previously introduced by Latora and Marchiori (33):…”
Section: Available Types Of Analysismentioning
confidence: 99%
See 3 more Smart Citations